1995
DOI: 10.1155/tsm.24.167
|View full text |Cite
|
Sign up to set email alerts
|

Texture and Properties of αAl2O3 Substrates

Abstract: Texture formation in Al203 substrates after green forming and sintering was studied. The results can be well represented in a texture formation diagram in terms of the green texture and a sintering factor. The sintering factor is related to grain growth. It can be quantified in terms of sintering time and temperatur with a growth rate factor depending on boundary energy and mobility. Two different regions of sintering temperatures can be distinguished of which the high-temperature one is related to liquid phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 4 publications
0
20
0
Order By: Relevance
“…Finally the small particle size of the precursor powder (∅=150 nm) is also an important factor to provide the driving force for grain growth. Bocker et al [6] clearly showed that small particles are necessary to develop a strong texture. Here, the specimen sintered at 1600°C exhibits a texture strength almost 8 times higher than the sample sintered at 800°C.…”
Section: Ebsd Data Analysismentioning
confidence: 99%
“…Finally the small particle size of the precursor powder (∅=150 nm) is also an important factor to provide the driving force for grain growth. Bocker et al [6] clearly showed that small particles are necessary to develop a strong texture. Here, the specimen sintered at 1600°C exhibits a texture strength almost 8 times higher than the sample sintered at 800°C.…”
Section: Ebsd Data Analysismentioning
confidence: 99%
“…D URING sintering of tape cast products, which require high dimensional accuracy for the use of high-integrated components, an anisotropic shrinkage can be observed, [1][2][3][4] which is attributed to an anisotropic green microstructure. During tape casting, nonspherical particles are oriented caused by shearing and constrained drying [5][6][7] resulting in a higher sintering shrinkage in the thickness direction than in the lateral direction. However, samples composed of spherical particles also exhibit anisotropic shrinkage behavior during sintering.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Research subject was the texture development in different a-alumina (R 3c) substrate ceramics (circuit carrier ceramics) produced from the manufacturer CeramTech. 38 In the present work one set of these samples with different annealing times was analyzed with our novel FXD-CSD method. In the forming process different binder substances had been tested.…”
Section: Methodsmentioning
confidence: 99%
“…B€ ocker examined the influence of different manufacturing steps prior to sintering on texture development: batching, milling, and forming. B€ ocker et al [36][37][38] report a rather strong texture development. In a subsequent step the influence of the sintering time had been investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation